Preparation and properties of capric acid–stearic acid-based ternary phase change materials. Issue 40 (19th July 2021) - Du, Wenqing; Fei, Hua; He, Qian; Wang, Linya; Pan, Yucheng; Liu, Jingtao
Abstract : Two kinds of CA–SA-based ternary phase change materials (PCMs), namely, capric acid–stearic acid–palmitic acid (CA–SA–PA) and capric acid–stearic acid–octadecanol (CA–SA–OD), were prepared by the melting–blending method. Abstract : Two kinds of CA–SA-based ternary phase change materials (PCMs), namely, capric acid–stearic acid–palmitic acid (CA–SA–PA) and capric acid–stearic acid–octadecanol (CA–SA–OD), were prepared by the melting–blending method. By the step cooling curve method, the optimum mass ratio of the two PCMs were determined to be CA : SA : PA = 77.4 : 8.6 : 14.0 and CA : SA : OD = 81.9 : 9.1 : 9.0, and the crystallization temperatures were 19.20 °C and 23.90 °C, respectively. The phase transition temperatures as measured by DSC were 18.60 °C and 24.82 °C, and the latent heat of phase transition were 129.15 J g −1 and 161.74 J g −1, respectively. The results are in good agreement with those measured by the step cooling curve method. The chemical and crystalline properties of the two PCMs were analyzed by FT-IR and XRD. It was found that CA–SA is combined with PA or OD by physical action, and the components have good compatibility and form a good eutectic structure. In addition, the results of heat storage and heat release experiments and the 500 times of accelerated melting–solidification cycling test showed that the two kinds of PCMs have good heat resistance and thermal reliability. Therefore, the prepared CA–SA–PA and CA–SA–OD have good performance and great application potential in building energy saving and solar energy utilization.